Abortion, Sharia, and the Modern Muslim State: Reassessing Pakistan’s Legal Framework - Areeba Iqbal Qureshi; Muhammad Zia-ul-Haq; Syed Naseeruddin Tahil; Muhammod Hazrat Imamnagar; Salman Chowdhury (Indonesian Journal of Islamic Law, 2025)
Abortion continues to represent one of the most debated issues in Islamic legal and ethical discourse, raising questions not only of public health but also of religious interpretation and human rights. In Pakistan, abortion is regulated under the Penal Code, yet its provisions remain highly ambiguous, particularly concerning the notions of “good faith” and “necessary treatment”. This study employs a qualitative doctrinal legal analysis, drawing on primary sources of Islamic law, contemporary fatwas, constitutional provisions, and international legal instruments, to examine the degree to which Pakistan’s abortion laws align with the objectives of maqāṣid al-sharīʿah. Anchored in the principles of preserving life (ḥifẓ al-nafs), faith, intellect, lineage, and property, the analysis incorporates Jasser Auda’s systems-based approach to demonstrate the dynamic potential of maqāṣid in addressing modern bioethical challenges. Findings reveal that Pakistan’s restrictive framework, shaped largely by colonial legacies, often compels women to seek unsafe abortions, thereby undermining the maqāṣid imperative of protecting life and dignity. The legal ambiguity surrounding organ formation and the undefined criteria of necessity stand in contrast with the Hanafi school’s permissibility of abortion before ensoulment (120 days) under legitimate grounds. Comparative insights from Muslim-majority states such as Tunisia, Morocco, and Iran show that more contextually adaptive laws can balance religious ethics with women’s health needs. The study concludes that substantive legal reform is required to harmonise Pakistan’s abortion laws with both Islamic objectives and international human rights standards. Such reform would provide legal clarity, safeguard maternal health, and restore coherence between Pakistan’s identity as an Islamic republic and its global human rights commitments.